2002
DOI: 10.1097/00005392-200210010-00024
|View full text |Cite
|
Sign up to set email alerts
|

Hemiscrotectomy With Contralateral Testicular Transposition for Scrotal Cancer

Abstract: In appropriate candidates this technique allows the scrotal defect to be easily reconstructed after tumor excision without any need for skin flaps or free skin grafts. The procedure makes it possible to preserve the scrotal content and perform more radical treatment since the scrotal wall is completely excised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Diagnosis is established by biopsy and the primary modality of therapy is surgery in the form of wide local excision with a safe margin of 3–5 cm in order to achieve R0 resection (microscopically free margin) along with ilio-inguinal block dissection on the affected side [7,8]. The wide local excision in some patients may leave large defects amounting to hemiscrotectomy and the testes on the affected side may either have to be sacrificed for non availability of accommodation or translocated to the contra lateral hemiscrotum facilitating closure of the surgical wound and preservation of testes, as was done in the reported case [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis is established by biopsy and the primary modality of therapy is surgery in the form of wide local excision with a safe margin of 3–5 cm in order to achieve R0 resection (microscopically free margin) along with ilio-inguinal block dissection on the affected side [7,8]. The wide local excision in some patients may leave large defects amounting to hemiscrotectomy and the testes on the affected side may either have to be sacrificed for non availability of accommodation or translocated to the contra lateral hemiscrotum facilitating closure of the surgical wound and preservation of testes, as was done in the reported case [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma is a neoplasm of the keratinising cells that show malignant characteristics including anaplasia, rapid growth, local invasion and metastatic potential. The treatment recommended for SCC is surgery in the form of wide local excision and block dissection of the draining lymph nodes [6-9]. …”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have reported various methods to cover a healthy testis when primary closure is not feasible. These include immediate use of local thigh flaps, 18 myocutaneous gracilis or adductor minimus myocutaneaus flaps, and heterologous fascia grafts. 1921 …”
Section: Introductionmentioning
confidence: 99%
“…15,22,23 Others do contralateral testicular transposition following a hemiscrotectomy. 24 Local recurrence may occasionally occur and may be due to insufficient tumor resection or may represent new lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation